Efecto de diferentes tipos de hidrocoloides en el tiempo de estabilidad de una bebida refrescante de limón (Citrus Limon) con panela - Álvarez Albia, Gean Carlos (2020)
The purpose of this research was to evaluate the different types of hydrocolloids based on the physicochemical and sensory properties of a refreshing lemon drink with panela. A completely randomized design (DCA) in a two-factor A * B arrangement was used. Factor A: Type of stabilizers (guar gum and xanthan gum); Factor B: Percentages of stabilizers (1%, 2% and 3%), which originated six treatments, three repetitions were performed, resulting in 18 experimental units of 1000g. The variables were based on stability based on the indicators of the refreshing drink: viscosity, spectrophotometry, acidity, density, pH and ° Brix, whose results were evaluated using linear regression analysis. Sensory análisis (ranking by preference) was performed by a panel of 75 untrained judges whose results were analyzed using a non-parametric Friedman analysis of variance, where a greater preference for treatments two and five was evident.